Cellular changes in the prostatic stroma of glucocorticoid-treated rats - Ribeiro, D. L.; Rafacho, A.; Bosqueiro, José Roberto [UNESP]; Taboga, S. R. [UNESP]; Goes, R. M. [UNESP] (Springer, 2008)
Glucocorticoid hormones (GCs) have been widely used for the treatment of prostate cancer because of their inhibitory property against tumour growth. However, their mechanism of action in the prostate has received little attention. Excess GCs can lead to peripheral insulin resistance resulting in hyperglycaemia and hyperinsulinaemia. Insulin plays an important role as a cellular stimulant and high levels are related to low levels of androgens. Our objective has been to describe the effects of insulin resistance induced by dexamethasone treatment on the morphology of rat ventral prostate. Mate adult Wistar rats received daily intraperitoneal injections of dexamethasone or saline for five consecutive days after which the rats were killed and the ventral prostate was removed, weighed and prepared for conventional and transmission electron microscopy (TEM). Dexamethasone treatment resulted in atrophy and decreased proliferative activity of prostatic epithelial cells. TEM analysis revealed changes in the epithelium-stroma interface, with some interruptions in the basement membrane. Fibroblasts showed a secretory phenotype with dilated endoplasmic reticulum. Smooth muscle cells exhibited a contractile pattern with 50% atrophy, an irregular membrane and twisted nuclei. Mitochondrial alterations, such as enlarged size and high electron density in the mitochondrial matrix, were also detected in smooth muscle cells. Insulin resistance induced by dexamethasone is thus associated with epithelial atrophy similar to that described for diabetic rats. However, GCs are responsible for morphological changes in the stromal cell population suggesting the activation of fibroblasts and atrophy of the smooth muscle cells.
Keywords: Prostate; insulin resistance; Glucocorticoid; stroma; Smooth muscle cells; Rat (Wistar)